2004
DOI: 10.1103/physrevlett.93.263201
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Potential and Kinetic Electron Emission for Grazing Impact of Multiply Charged Ar Ions on a LiF(001) Surface

Abstract: Projectile time-of-flight spectra and the number of emitted electrons have been determined in coincidence for grazing scattering of slow (0.45 keV/u) multiply charged Ar ions from an atomically clean and flat LiF(001) surface. By relating projectile energy loss to kinetic electron emission we were able to determine contributions from potential electron emission even in the presence of a considerable number of kinetically excited electrons. Our results suggest a practically complete use of the available potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Secondary-electron emission measured in coincidence with no kinetic energy loss of incident ions was reported by Stöckl et al [3]. It was the first observation of pure potential emission of secondary electrons induced with HCIs.…”
Section: Introductionmentioning
confidence: 81%
“…Secondary-electron emission measured in coincidence with no kinetic energy loss of incident ions was reported by Stöckl et al [3]. It was the first observation of pure potential emission of secondary electrons induced with HCIs.…”
Section: Introductionmentioning
confidence: 81%
“…Figure 5 demonstrates a linear relationship between "pure" PE yields and the potential energy E pot brought towards the surface by the different MCI. There is no dependence on the ion kinetic energy, although it has been varied between 18 and 54 keV [29]. In addition, data points are situated right at the border of the region allowed by potential energy conservation (shaded triangular area in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Extrapolation of the respective curve to the hypothetical case of no energy loss (not directly observable in our experiment!) corresponds to an electron emission yield which is not associated with any kinetic energy loss of the projectile [29]. Since these electrons have not been emitted at the expense of the projectile kinetic energy, they can only result from deposition of projectile potential energy E pot , and thus give rise to the "pure" potential electron emission yield γ P E (ΔE → 0).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Hughees et al [9] separated the kinetic and potential electron emission and concluded that the dominant potential emission mechanism is Auger processes within the target bulk. By using coincidence techniques Lemell et al [10] and Stockl et al [11] separated the PE and KE contributions for argon ions impact on Au and LiF surfaces. Besides the separated of PE and KE contributions, Delaunay et al [12] confirmed that most electrons emitted by highly charged ions have low energies and the total electron yields increase linearly with the potential energy of the projectile.…”
Section: Introductionmentioning
confidence: 99%